A seed-like hydrogel with metabolic cascade microbiota for oral treatment of liver failure. (September 2022) - Zheng, Di-Wei; Chen, Ke-Wei; Yan, Jian-Hua; Rao, Zhi-Yong; Yang, Chi-Hui; Li, Rui-Lin; Tang, Ying; Cheng, Han; Zhang, Xian-Zheng
Graphical abstract: A seed-like hydrogel with metabolic cascade microbiota was demonstrated to achieve efficient oxygen consumption and cascaded hypoxia-induced ammonia elimination, which can reduce hepatotoxic endotoxin and neurotoxic ammonia in situ in the non-invasive treatment of liver failure. Abstract: Liver failure is a fatal disease with a mortality rate of 80%. The only access to treat liver failure is invasive operation, which is restricted by limited donor sources or high costs. Thus, non-invasive medication for liver failure is urgently needed. Herein, we tried the first attempt to design a seed-inspired hydrogel with a micro-ecosystem, which imitates characteristics of seed with high intestinal adaptability, for the elimination of harmful metabolites in liver failure using a cascade reaction triggered by encapsulated microbes. Focusing on abnormal ammonia assimilation and intestinal oxygen metabolism, a two-component artificial microbiota was constructed to enable efficient intestinal oxygen consumption and subsequent hypoxia-induced ammonia elimination. More importantly, we imitated plant seeds with high adaptability to the intestinal environment to improve the performance of bacteria. A hydrogel particle with the seed shape, lignin coating, and porous structure, for achieving intentional retention, bacterial protection, and diffusion promotion, respectively was prepared. In murine and porcine models of liver failure, the artificial reactor lowered the blood ammonia to prevent nerve damage, and consumed oxygen to inhibit pathogenic facultative anaerobes for alleviating liver failure. This work underscores the great potential of medication with a bioinspired micro-ecosystem for liver failure.